Pelatihan Pengolahan Limbah Plastik pada Umat Buddha di Kabupaten Wonogiri - Danang Try Purnomo; Hesti Sadtyadi; Santi Paramita; Sugik Harto; Ratna Setyaningsih (Jurnal Ilmiah Pengabdian dan Inovasi, 2026)
The community service program held in Jendi Village, Girimarto District, Wonogiri Regency, was titled plastic waste processing training. The community service activity was carried out with the aim of implementing plastic waste management through educational activities and mentoring on managing plastic waste into items of economic value. This activity also aims to mitigate the impact of environmental damage caused by plastic waste. The method used in the community service was a participatory approach. This approach was carried out by involving the service team and the community in managing plastic waste. The location used was the Vimalakirti Temple complex, Jendi Village, Girimarto District. Meanwhile, the subjects assisted in the implementation of the service were Buddhists and residents of Jendi Village. This community service activity produced three results. First, the establishment of an ecosystem that cares about waste, especially plastic waste. Second, the realization of community understanding regarding how to sort plastic waste. Third, the community was educated about plastic waste management to generate economic benefits and have an impact on efforts to prevent environmental damage caused by plastic waste.